EXAMINING THE SOCIAL BEHAVIOR OF ANT COLONIES USING COMPLEX NETWORKS - MURSA, Bogdan (Studia Universitatis Babeș-Bolyai Informatica, 2023)
This paper proposes the use of Complex Network Theory to model the interactions between ants and analyze their social behavior. Specifically, the study focuses on six colonies of ants to investigate whether their behavior is community-oriented or individual-oriented. The research employs various nodes properties that define nodes’ importance to quantify the existence of a social or individual-oriented behavior. The results aim to provide insights into the social behavior of ants and may have implications for understanding other complex social systems. Received by the editors: 17 March 2023. 2010 Mathematics Subject Classification. 05Cxx, 93Bxx, 92-xx. 1998 CR Categories and Descriptors. E.1 [Data]: Data Structures – Graphs and networks; G.2.2 [Discrete mathematics]: Graph Theory – Network problems (G.2.2).